2006
DOI: 10.1073/pnas.0600525103
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences between galactolipids and glucolipids revealed in photosynthesis of higher plants

Abstract: Galactolipids represent the most abundant lipid class in thylakoid membranes, where oxygenic photosynthesis is performed. The identification of galactolipids at specific sites within photosynthetic complexes by x-ray crystallography implies specific roles for galactolipids during photosynthetic electron transport. The preference for galactose and not for the more abundant sugar glucose in thylakoid lipids and their specific roles in photosynthesis are not understood. Introduction of a bacterial glucosyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Another chloroplast galactolipid, DGDG, has also been found in the crystallized PSII complex and in LHCII (5,15). Analyses of a dgd1 mutant in which DGDG content is significantly depleted indicated that DGDG plays a crucial role in PSII activity and the stabilization of trimeric LHCII (16)(17)(18). The dgd1 mutant also demonstrated the importance of DGDG for the stability and activity of the PSI complex (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…Another chloroplast galactolipid, DGDG, has also been found in the crystallized PSII complex and in LHCII (5,15). Analyses of a dgd1 mutant in which DGDG content is significantly depleted indicated that DGDG plays a crucial role in PSII activity and the stabilization of trimeric LHCII (16)(17)(18). The dgd1 mutant also demonstrated the importance of DGDG for the stability and activity of the PSI complex (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…The cDNAs from Arabidopsis DGD1, DGD2, and Chloroflexus GlcT (5,8,15,19,20,45,46) were cloned into E. coli expression vectors for lipid measurements and lipid binding or liposome aggregation experiments (31,47) or into binary vectors (48) for Arabidopsis transformation (SI Appendix, SI Material and Methods). The Arabidopsis dgd1-1 mutant was transformed using the Agrobacterium floraldip method (49).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the relevance of NDGD1 for glycolipid production in planta was studied by introducing NDGD1 constructs or chloroplast envelope-targeting sequences of MGD1 (NM1, targeting the inner envelope) or DGD2 (ND2, a short N-terminal sequence targeting the oEM), fused to CDGD1, DGD2, or a glucosyltransferase, GlcT, from Chloroflexus aurantiacus, into dgd1-1. GlcT adds a glucose to carbon 6 of the galactose moiety of MGDG, thereby producing GlcGalDG (19). The synthesis of DGDG or GlcGalDG was monitored by TLC separation and quantification by GC (Fig.…”
Section: Ndgd1 Is Essential For Dgdg Mobilization From the Oem To Thementioning
confidence: 99%
“…This led to various defects in the mutant, especially the dwarf phenotype, mainly because of overproduction of oxylipin and lignification of the phloem cap (Lin et al, 2016). These phenomena were partially complemented by introducing Chloroflexus aurantiacus glycosyltransferase (β-GlcT) (Hölzl et al, 2006(Hölzl et al, , 2009, which synthesizes…”
Section: Molecular Species and Configuration Of The Sugar Head In Digmentioning
confidence: 99%